Penerapan Metode Whole Brain Teaching dalam Meningkatkan Motivasi Belajar Anak Usia Dini - Choirun Nisak Aulina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The aims of this research are to improve children's learning motivation through the implementaion of Whole Brain Teaching and to describe the improvement of children's learning motivation through the implementation of Whole Brain Teaching. This research is a classroom action research, then research subjects consisted of 18 students at TK Aisyiyah 1 Tanggulangin, especially group A. The location of this research is in TK Aisyiyah 1 Tanggulangin. Data collection technique is done by observation. The results show that the implementation of Whole Brain Teaching method can improve the learning motivation of students at TK Aisyiyah 1 Tanggulangin. It  can be seen from the improvement of children's learning motivation from the state of the 33% grade completeness score in the pre cycle, up to 56% in cycle I, then 83% grade mastery score in cycle II. So in accordance with the level of completeness of the action that the score of 75% -100% is in very good qualifications and the implementation of the action declared successful